Bone Involvement by Adenocarcinoma of the Uterine Cervix: A Rare Entity - Crisci, Vincenzina (Pol J Radiol, 2015)
BACKGROUND: Adenocarcinoma is the second most frequent cancer of the uterine cervix after squamous carcinoma, and the most frequent histotype is the mucinous one. Endo-cervical adenocarcinoma accounts for about 10–30% of all cervical cancers and clinically the lesion can be asymptomatic or, more frequently, presenting with anomalous bleeding and/or vaginal discharge. CASE REPORT: A 41-year-old woman with a diagnosis of adenocarcinoma of the uterine cervix was subjected to chemotherapy after radical surgery. During the follow-up, the patient underwent a Positron Emission Tomography integrated with Computed Tomography and pelvic Magnetic Resonance, which showed rapid and diffuse disease progression from the site of the lesion to the pelvic bones. CONCLUSIONS: Bone involvement in patients with cervical cancer, being a rare event, is significant since it greatly reduces life expectancy. The majority of metastatic bone lesions in cervical cancer seem to be of osteolytic nature. In our patient, Positron Emission Tomography integrated with Computed Tomography and Magnetic Resonance were the imaging methods used during the follow-up and both techniques clearly showed diffuse and rapid tumour spread to the bones.